2008
DOI: 10.1111/j.1473-2165.2008.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐lightening effects of a new face care product in patients with melasma

Abstract: The data demonstrate that the new face care product is effective and highly skin tolerable and clearly improves quality of life of patients with melasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
(29 reference statements)
2
13
0
Order By: Relevance
“…Data provided by Scherdin et al 9 . showed that the MASI score decreased by 42.3% from baseline to the end of the study with DA after 8 weeks of treatment, comparable with the results of 2% HQ.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Data provided by Scherdin et al 9 . showed that the MASI score decreased by 42.3% from baseline to the end of the study with DA after 8 weeks of treatment, comparable with the results of 2% HQ.…”
Section: Discussionsupporting
confidence: 69%
“…Data provided by Scherdin et al 9 showed that the MASI score decreased by 42.3% from baseline to the end of the study with DA after 8 weeks of treatment, comparable with the results of 2% HQ. This was the first study on the efficacy of DA in melasma, and demonstrated that DA is an effective and highly skin-tolerable product.…”
Section: Discussionsupporting
confidence: 66%
“…Both the vehicle‐ and the PKEK‐containing formulation improved the evenness of skin coloration and overall skin appearance compared with the baseline skin condition, but the PKEK treatment was found to be superior and significantly different to the vehicle after 12 weeks of treatment. There have been many studies examining the effect of agents on melasma and the efficacy ranged from approximately 15–70% improvement using the Melasma Area and Severity Index (MASI) or others have used the mexameter 32 . We used a different grading scale in our studies, as the subjects also had postinflammatory hyperpigmentation from acne and as such cannot directly compare with previous results.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies examining the effect of agents on melasma and the efficacy ranged from approximately 15-70% improvement using the Melasma Area and Severity Index (MASI) or others have used the mexameter. 32 We used a different grading scale in our studies, as the subjects also had postinflammatory hyperpigmentation from acne and as such cannot directly compare with previous results. Nevertheless, clearly, the PKEK-containing formulation was highly efficacious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation